Purple potato extract modulates fat metabolizing genes expression, prevents oxidative stress, hepatic steatosis, and attenuates high-fat diet-induced obesity in male rats - Ishrat Jahan; Asif Ul Haque Shuvo; Mirza Alimullah; A. S. M. Nafiur Rahman; Shahnaz Siddiqua; Shatil Rafia; Ferdous Khan; Khondoker Shahin Ahmed; Hemayet Hossain; Kazi Akramuddaula; Md Ashraful Alam; Nusrat Subhan (PLoS ONE, 2025)
Objective In this investigation, the significance of purple potato (Solanum tuberosum L.) extract treatment was assessed against oxidative stress and fat metabolizing transcription factors in the liver of high-fat (HF) diet-fed rats. Methods Wistar (male) rats were arranged into several groups and provided with a control and HF diet along with the purple potato extract. Body weights, oral glucose tolerance test (OGTT), insulin, plasma lipids, and oxidative stress-related indicators were analyzed in plasma and tissue samples. Additionally, real-time PCR was performed to evaluate the gene expression for oxidative stress and fat metabolism in the liver. Histological staining was also performed on pancreatic and hepatic tissues. Results Purple potato extract lowered body weights and improved glucose utilization in the OGTT test in HF diet-fed rats. Purple potato extract also suppressed HF-diet-induced oxidative stress in plasma and hepatic tissues. Purple potato extract also restored the Nrf-2 expression in the liver, followed by the improved expression of HO-1, HO-2, and other antioxidant genes in HF diet-fed rats. In addition, genes involved in lipid metabolism were also positively modulated due to purple potato extract treatment. Furthermore, histological examination revealed the reduction of lipid accumulation and amelioration of inflammation due to the consumption of purple potato extract. Conclusion This investigation revealed that antioxidant-rich purple potato extract can modulate the antioxidant and fat metabolizing genes expression, ameliorated oxidative stress and glucose intolerance as well as lowered blood lipids in male rats.